Indocyanine green clearance of remnant liver (ICG-Krem) predicts postoperative subclinical hepatic insufficiency after resection of colorectal liver metastasis: theoretical validation for safe expansion of Makuuchi's criteria. Issue 2 (February 2020) - Kobayashi, Yuta; Kiya, Yoshitaka; Nishioka, Yujiro; Hashimoto, Masaji; Shindoh, Junichi
Abstract: Background: Multidisciplinary treatment for colorectal liver metastases (CLMs) often includes major hepatectomy for preoperative chemotherapy-related hepatic injury, although the safety limit for resection extent is unclear. We investigated this parameter using the estimated indocyanine green clearance rate (ICG-K) of liver remnants, focusing on postoperative subclinical hepatic insufficiency (PHI). Methods: Altogether, 225 patients who underwent resection of CLMs were studied. The predictive power of estimated ICG-K of liver remnant (ICG-Krem) for subclinical PHI (peak bilirubin ≥3 mg/dL or refractory ascites) was compared with those of other potential predictors. The suggested safety limit of ICG-Krem ≥0.05 was also assessed. Results: Receiver-operating curve analysis revealed that ICG-Krem [area under the curve (AUC) 0.752, cutoff 0.102] was the best predictor of subclinical PHI (AUC range for others was 0.632–0.668). Makuuchi's criteria corresponded to ICG-Krem 0.10. Subclinical PHI incidence was significantly elevated at ICG-Krem <0.10 (26% vs 8%, p = 0.002), while potentially fatal PHI (peak bilirubin >7 mg/dL) was not observed until down to ICG-Krem of 0.05. Conclusions: ICG-Krem sensitively predicts subclinical PHI. Liver failure-related death could be avoided so long as ICG-Krem remains at ≥0.05. However, patients with ICG-Krem 0.05–0.10 are at high risk of subclinical PHI and require intensive care postoperatively.